2005
DOI: 10.4049/jimmunol.175.12.8077
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Lipid Rafts Stimulates Phospholipase D Activity in Human Lymphocytes: Implication in the Regulation of Immune Function

Abstract: Recent evidence suggests that phospholipase D (PLD) can be regulated through its association/dissociation to lipid rafts. We show here that modifying lipid rafts either by cholesterol depletion using methyl-β-cyclodextrin and filipin or by conversion of sphingomyelin to ceramide with exogenous bacterial sphingomyelinase (bSMase) markedly activated the PLD of human PBMC. bSMase was the most potent PLD activator, giving maximal 6- to 7-fold increase in PLD activity. Triton X-100-treated lysates prepared from con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 56 publications
3
22
0
Order By: Relevance
“…4). These results support further our current hypothesis that PLD activity conveys antiproliferative signals in lymphoid cells [8,15] and suggest that 20:5n-3 inhibits thymocyte proliferation by a particular mechanism unrelated to that of the other FAs.…”
Section: In Vitro Effects Of Fas On Thymocyte Phospholipase D Activitysupporting
confidence: 82%
See 1 more Smart Citation
“…4). These results support further our current hypothesis that PLD activity conveys antiproliferative signals in lymphoid cells [8,15] and suggest that 20:5n-3 inhibits thymocyte proliferation by a particular mechanism unrelated to that of the other FAs.…”
Section: In Vitro Effects Of Fas On Thymocyte Phospholipase D Activitysupporting
confidence: 82%
“…In contrast, when lymphocyte membranes were enriched with docosahexaenoate or 12-HETE prior to mitogenic stimulation, PLD was activated, leading to an inhibition of the proliferation response. The hypothesis that PLD is antiproliferative in lymphoid cells has been strongly reinforced by our recent work showing that overexpression of the PLD1 isoform in Jurkat cells inhibits IL-2 mRNA expression in response to phorbol 12-myristate 13-acetate (PMA) and ionomycin activation [15].…”
Section: Introductionmentioning
confidence: 97%
“…It is noteworthy that fibroblasts express endogenous PLD1 and PLD2. A study of overexpression of PLD1 and PLD2 in Jurkat T-cells, using transient transfection, concluded that PLD1 (but not PLD2) impairs mitogenic signaling (Diaz et al, 2005). The Jurkat cell line used expresses endogenous PLD2 but low levels of PLD1.…”
Section: Discussionmentioning
confidence: 99%
“…on May 12, 2018 by guest http://mcb.asm.org/ Previous work has shown that PLD2 may be associated with cholesterol-dependent plasma membrane nanodomains, commonly called lipid rafts (10), and that cholesterol depletion leads to PLD2 activation (11). Collecting these data together with the new results presented in this paper, we propose that PLD2 is a cholesterol-sensitive regulator of the Ras/MAPK signaling pathway.…”
mentioning
confidence: 69%